Exploration of academic culture in Iranian higher education institutions based on Grounded Theory - F. Asghari (Taḥqīqāt-i Farhangī-i Īrān)
Like any other community, the university has its own cultural set up. But unfortunately, the culture, which is currently dominating the Iranian higher education institutions, does not meet the expectations of a scientific community. The present study, based on views and experiences of academics as well as using an interpretive approach, tries to answer the main research question as why and how such a disorder prevails in academic culture. In this qualitative study, the Grounded Theory has been applied as research methods. The selection of participants, including faculty members from higher education institutions, was based on theoretical sampling. It continued until achieving a saturation point. Data collection was done through semi-structured interviews, including 17 individual and 4 group interviews. Data were categorized via three-stage coding (open, axial and selective) and classified into 1900 codes, 458 concepts, 101 subcategories and 32 main categories. Further, the data analysis was carried out based on the concept of context, analytical tool paradigm (conditions, action-interaction and consequences) and conditional-consequential analytical strategy matrix. Based on the acquired results "non-adherence to academic norms" was selected as a central phenomenon, and the final model was based on causal conditions and contextual factors at micro and macro levels, academic interaction including resistance, silence and abuse as well as the consequences including individual, organizational and national ones. The final outcome indicates the strengthening and reproduction of the central phenomenon in case of lack of university actions to help improve the situation.